Metagenomic insights into resistance trends related to microbial VB12 synthesis in eutrophic urban lakes - Ning Lan; Chengzhi Mao; Min Chen; Xuan Wang; Shuheng Bai; Juan Ren (Scientific Reports)
Abstract Vitamin B12 (VB12) is essential for human health, and its deficiency can lead to various health issues, including anemia and neurological problems. Additionally, the presence of antibiotic resistance genes in various environments raises concerns about the spread of antibiotic resistance. This study aims to explore potential connections between these two functional gene categories in freshwater environments, which are closely intertwined with human health. We conducted a comprehensive metagenomic sequencing analysis across 23 sampling points from five different eutrophic urban lakes. The results highlight the dominance of the precorrin-2 synthesis pathway in the microbial synthesis of VB12 within urban lakes. Eutrophication may potentially enhance the precorrin-2 synthesis pathway while inhibiting others. The risk of antibiotic resistance is reduced in the anaerobic pathway of VB12 synthesis, while the abundance of metal resistance genes is increased. Binning analysis reveals that 26 metagenome-assembled genomes (MAGs) actively participate in VB12 synthesis, with at least 4 MAGs showing resistance during the VB12 synthesis process and demonstrating pathogenicity. These findings provide critical insights into the VB12 synthesis process and its implications for human health in terms of resistance risks.